2018
DOI: 10.1212/wnl.0000000000004932
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neurofilament light chain concentration in the inherited peripheral neuropathies

Abstract: ObjectiveTo perform a cross-sectional study to determine whether plasma neurofilament light chain (NfL) concentration is elevated in patients with Charcot-Marie-Tooth disease (CMT) and if it correlates with disease severity.MethodsBlood samples were collected from 75 patients with CMT and 67 age-matched healthy controls over a 1-year period. Disease severity was measured using the Rasch modified CMT Examination and neuropathy scores. Plasma NfL concentration was measured using an in-house-developed Simoa assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
206
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(261 citation statements)
references
References 23 publications
18
206
9
Order By: Relevance
“…Hopefully, in the nearby future, new diagnostic tools may become available. Recently, attention has been paid to neurofilament light chain as potential marker of peripheral nerve damage both in the preclinical and clinical setting . A possible diagnostic and prognostic role of neurofilaments in the polyneuropathies workup is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Hopefully, in the nearby future, new diagnostic tools may become available. Recently, attention has been paid to neurofilament light chain as potential marker of peripheral nerve damage both in the preclinical and clinical setting . A possible diagnostic and prognostic role of neurofilaments in the polyneuropathies workup is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…57 NEFL assays in CMT has provided an important marker of axonal degeneration in CMT1A, 9 but there is currently a lack of biomarkers to assess disease processes in the SCs that are most directly affected by the PMP22 gene duplication. Biomarkers can be used to not only measure disease process (NEFL levels) and disease burden (MRI), but also target engagement for a given therapy.…”
Section: Discussionmentioning
confidence: 99%
“…2 A recent study using antisense oligonucleotides showed dramatic improvement in a severe mouse model of CMT1A as well as a more mild rat model of the disease. 7,8 In addition, neurofilament L protein (NEFL) levels are elevated in CMT1A plasma samples and correlate with severity as measured by the CMTNS-R and CMTES-R. 9 Given that several candidate therapeutic strategies are aimed to reduce PMP22 mRNA levels, 3,10 developing a robust method for establishing PMP22 mRNA levels from skin biopsies would be a valuable marker of target engagement for clinical trials in CMT1A. 4 Clinical outcome assessments, such as the Rasch modified CMT Neuropathy or Exam Scores (CMTNS-R/ CMTES-R), measure severity of neuropathy in adults and children with CMT1A.…”
mentioning
confidence: 99%
“…Following axonal damage, neurofilaments are released into the circulation and can be detected in the plasma using highly sensitive analytical methods such as the Single molecule array (Simoa) platform . We have previously shown that pNFL is raised in patients with Charcot‐Marie‐Tooth (CMT) disease and that it correlates with disease severity . In this study, we sought to determine whether pNFL was also raised in patients with ATTRm neuropathy compared to controls and if it correlates with disease severity and neuropathy scores.…”
Section: Introductionmentioning
confidence: 99%